PERTUMBUHAN SPIRULINA PADA BERBAGAI PERLAKUAN MEDIA KULTIVASI (REVIEW) - Damai Diniariwisan; Nuri Muahiddah (Jurnal Perikanan Pantura (JPP), 2024)
Potential using of single cell proteins in life increasingly has great potential. Spirulina sp. as a microalgae which contains high levels of nutrients such as protein, fat and minerals has become superior for cultivation. Many benefits in various fields, including fisheries, health, cosmetics and industry, have resulted in a lot of research being carried out to increase cultivation production. Various research sources have been summarized to find out how various media treatments influence the growth and density of spirulina. Through various cultivation media treatments and also the addition of various fertilizers as nutrients, variations in spirulina growth density are produced. In general, Spirulina sp. prefers media with normal pH that tends to be alkaline, namely 7-10. As for the salinity range, they are able to grow in high salinity range of 15-30 ppt. Application of organic and inorganic fertilizers can produce higher density. On a semi-mass media scale of 100 liters, the addition of a combination of ±100 g of inorganic fertilizer showed growth that continued to increase even until the 15th day. The use of organic fertilizer, especially from bird droppings, shows the highest density compared to chicken, cow and buffalo manure. Using organic fertilizer can be more recommended alternative, because it uses natural or organic ingredients that come from nature.